Aktivitas antibakteri (Pseudomonas aeruginosa dan Staphylococcus aureus) dari ekstrak etanol selada air (Nasturtium officinale) : Antibacterial activity (Pseudomonas aeruginosa and Staphylococcus aureus) of ethanol extract from watercress (Nasturtium officinale) - Hakim, Salman Khaerul; Sudirman, Sabri; Janna, Miftahul; Nugroho, Gama Dian; Sari, Dwi Inda (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2024)
Bacteria can adversely affect the quality of fishery products and pose a risk of disease in humans. Polyphenolic substances derived from plant extracts are promising sources of natural antimicrobial agents. The objective of this study was to assess the antimicrobial properties of polyphenolic compounds extracted from watercress (Nasturtium officinale) against Staphylococcus aureus and Pseudomonas aeruginosa. Polyphenolic compounds were obtained through maceration using 70% ethanol, and their concentrations were determined using the Folin-Ciocalteu method. Antibacterial activity was assessed using the Kirby-Bauer well diffusion method. The output obtained from the extraction process yielded 21.62±1.55% polyphenol content, amounting to 28.49 mg GAE/g of dry sample. The relationship between the sample concentration and its ability to inhibit bacterial growth was indicated by the results of the antibacterial assay, which revealed a direct proportionality between the two variables. The inhibition zone diameter at a concentration of 1 mg/mL for P. aeruginosa was measured to be 11.13 millimeters, while that for S. aureus it was measured at 8.98 millimeters. Based on these findings, polyphenolic substances derived from watercress can be utilized as natural antibacterial agents.